An investigation of antioxidative and anti-inflammatory effects of Taraxacum coreanum (white dandelion) in lactating Holstein dairy cows - Kim, Sung Jae; Jo, Young Jun; Jeong, Sang Hee; Kim, Yo Han; Han, Jeong Hee (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The aim of this investigation was to examine the impact of Taraxacum coreanum (known as dandelion) (TC) and TC mixtures with milk thistle (MT) or Aspergillus oryzae (AO) as feed additives on the immune response, milk quality, and milk production in Holstein cows over 6 weeks of administration. Materials and Methods: Thirty-two healthy Holstein dairy cows were provided 30 kg of total mixed ration (TMR) with no TC, 90 gm TC, 54 gm TC + 36 gm MT, or 54 gm TC + 36 gm AO 40% groups. The feed additives were supplied daily in two equal portions (per 45 gm) by topdressing the TMR for 6 weeks. Milk and blood samples were collected weekly. Results: In the TC-treated cows (TC, TC + MT, and TC + AO groups), significantly lower peripheral blood white blood cell (WBC) counts at 6 weeks and milk somatic cell counts (SCCs) at 4–6 weeks of administration were observed. Concentrations of serum superoxide dismutase (SOD) and glutathione peroxidase (GSH-px) were notably elevated in cows treated with TC for 4–6 weeks, while levels of proinflammatory cytokines concentrations of tumor necrosis factor-alpha (TNF-α) and chemokine (IL-8) were significantly reduced in TC-treated cows after 3–6 weeks of administration. Conclusion: These results suggested that TC or a TC mixture with other medicinal herbs supplementations enhanced the serum antioxidative activities and, consequently, might suppress the adverse immune response due to lower serum TNF-α and IL-8 release supported by lower WBC and SCC counts. Adv. Vet. Anim. Res., 11(2): 330-338, June 2024 http://doi.org/10.5455/javar.2024.k781